Student Learning Motivation in Post-New Normal Pjok Learning at SMP Negeri 2 Kutawaluya - Raka Adhitya Dhermawan; Citra Resita; Bambang Ismaya; Abdul Salam Hidayat (Peneliti.net, 2022)
The COVID-19 pandemic has had a major impact on the education sector, especially in Indonesia. Changes in the learning system to be online with all the limitations and conditions of students in each region affect students' learning motivation. Until finally, Indonesia was slowly able to end the wave of Covid-19 transmission. Entering the post-new normal period, the learning system was changed back to face-to-face. This study focuses on the level of student learning motivation within the scope of PJOK. This research was conducted at SMP Negeri 2 Kutawaluya with a sample of 76 people. The method used in this research is a survey method in the form of a questionnaire which is distributed directly to students. The purpose of this study is to determine the level of learning motivation of SMP Negeri 2 Kutaluya students in learning PJOK after the new normal period